Validação dos questionários Foot and Ankle Ability Measure (FAAM) e Foot and Ankle Outcome Score (FAOS) para Instabilidade Crônica de Tornozelo - Silva, Gabriella Teixeira (2024)
Chronic ankle instability (CAI) is a condition commonly observed in physically active individuals, who present recurrent lateral ankle sprains, a sensation of distortion, pain and swelling, and may present biomechanical changes and changes in the functionality of the ankle and foot. According to The International Ankle Consortium (IAC), some selection criteria for individuals with ICT have been established. Among these specifications, the IAC guides the use of evaluative and discriminative perception questionnaires. The Identification of Functional Ankle Instability (IdFAI), as an instrument for selecting individuals with CAI, and the Foot and Ankle Ability Measure (FAAM) and Foot and Ankle Outcome Score (FAOS), which check the functionality of the ankle and foot, are the most used. However, in order to use patient-reported measurement instruments (PROM's), it is necessary to evaluate and measure the measurement properties to verify whether the PROM's are capable of effectively measuring their domains and subscales under certain conditions. Despite this, the FAAM and FAOS presented methodological deficits and measurement properties not yet presented for active individuals with CAI, which would impact the assessment of functionality. The objective of the study was to validate the FAAM and FAOS instruments for physically active individuals with CAI based on the recommendations of the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN). 167 volunteers were evaluated, separated into a structural and construct validity group, a reliability group, both with CAI and a control group, in which a sports and injury characterization form and the IdFAI, FAAM and FAOS questionnaires were applied to classify all individuals according to their inclusion criteria for research. For statistical analysis, the structural validity of the FAAM and FAOS subscales was tested through confirmatory factor analysis, intraclass correlation coefficient, hypothesis tests, internal consistency analysis, measurement error and minimum important change. The results indicate that the FAAM and FAOS questionnaires are reliable and validated to be applied to the active population with CAI to assess functionality according to the COSMIN criteria. Furthermore, the FAOS-Sport and FAOS-Quality of life subscales are able to discriminate individuals with CAI with a score for each subscale.